2001
DOI: 10.3102/00028312038003653
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Teachers’ Generative Change: A Follow-Up Study of Professional Development in Mathematics

Abstract: This study documents how teachers who participated in a professional development program on understanding the development of students’ mathematical thinking continued to implement the principles of the program 4 years after it ended. Twenty-two teachers participated in follow-up interviews and classroom observations. All 22 teachers maintained some use of children’s thinking and 10 teachers continued learning in noticeable ways. The 10 teachers engaged in generative growth (a) viewed children’s thinking as cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
189
0
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(205 citation statements)
references
References 24 publications
9
189
0
7
Order By: Relevance
“…Furthermore the inductive and practical approach to sociocultural theory of teaching and learning introduced in this paper could be continued as a part in-service practice. The threat does exist that real school culture could lead to regression; however, some teachers working independently in their classes have demonstrated the ability to continue professional development when well-prepared for reform (Franke, Carpenter, Levi, & Fennema, 2001). In Franke et al's study, teachers kept pupil thinking in the center when it came to their beliefs and practice about teaching and learning.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore the inductive and practical approach to sociocultural theory of teaching and learning introduced in this paper could be continued as a part in-service practice. The threat does exist that real school culture could lead to regression; however, some teachers working independently in their classes have demonstrated the ability to continue professional development when well-prepared for reform (Franke, Carpenter, Levi, & Fennema, 2001). In Franke et al's study, teachers kept pupil thinking in the center when it came to their beliefs and practice about teaching and learning.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a follow-up study of the successful Cognitively Guided Instruction professional program for elementary mathematics teachers found that in schools where teachers continued to talk together about student thinking in mathematics, as part of teacher teams in their schools, they were able to sustain improvements to their practices (Franke et al 2001). In a different context, in which policy shifts reduced the availability of professional development available to teachers, some schools were able to sustain ongoing teacher learning opportunities when there were high numbers of content-focused teachers in a school and when teachers share a common vision for instructional practice (Kaufman and Stein 2010).…”
Section: Using Social Network Analysis To Model Teacher Learning Frommentioning
confidence: 99%
“…Diversi studi attestano l'efficacia di interventi video-based nella formazione degli insegnanti (Santagata, Zannoni, & Stigler, 2007). Il video è stato riconosciuto come (i) valido all'interno di pratiche di modellamento, in quanto non soltanto fornisce un'esemplificazione della pratica, ma impegna gli studenti in un processo di analisi complesso e riflessivo (Santagata & Guarino, 2011); (ii) utile promotore di una riflessione generale e personale -nel caso di auto-analisi -sulla didattica (ad esempio nella pratica del microteaching) (van Es & Sherin, 2002); (iii) efficace strumento in grado di far focalizzare l'attenzione sugli studenti (ad esempio nel video club) (Franke et al, 2001;Santagata et al, 2007;van Es & Sherin, 2008).…”
Section: Il Video-coaching: Strumento DI Auto-riflessivitàunclassified